Change of Bearing Capacity Characteristics of Asphalt Pavement - Jozef Komacka (Communications - Scientific letters of the University of Zilina, 2011)
Time succession of data for monitored variable parameter of pavement state is the first step in development of degradation models and determination of degradation functions. Procedure used for characteristics of bearing capacity is described in the paper.Data from long time monitored (since 1995) test section on road network were used. First of all homogeneity of subgrade was tested. The deflections at distance of 1500 mm from load centre were used for this purpose. Data that met criteria of homogeneity were corrected taking into account influence of temperature. Two characteristics of bearing capacity (central deflection and surface curvature index) were evaluated in relation to number of heavy vehicles that had passed test section.Results showed that investigated characteristics of pavement bearing capacity changed in time. It was stated that tendency of development was not very clear because values oscillated in the narrow range. Generally saying the bearing capacity of tested pavement has not changed since 1995 significantly.